If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(x + 2) = 12x + 1 Reorder the terms: 3(2 + x) = 12x + 1 (2 * 3 + x * 3) = 12x + 1 (6 + 3x) = 12x + 1 Reorder the terms: 6 + 3x = 1 + 12x Solving 6 + 3x = 1 + 12x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-12x' to each side of the equation. 6 + 3x + -12x = 1 + 12x + -12x Combine like terms: 3x + -12x = -9x 6 + -9x = 1 + 12x + -12x Combine like terms: 12x + -12x = 0 6 + -9x = 1 + 0 6 + -9x = 1 Add '-6' to each side of the equation. 6 + -6 + -9x = 1 + -6 Combine like terms: 6 + -6 = 0 0 + -9x = 1 + -6 -9x = 1 + -6 Combine like terms: 1 + -6 = -5 -9x = -5 Divide each side by '-9'. x = 0.5555555556 Simplifying x = 0.5555555556
| 4x-3-1x=x-5 | | q=12-3p | | 6(3x+4)=186 | | -7(5x-4)=413 | | 4x+17=2x+53 | | 3x/4x-2=8 | | 5x-3=x-15 | | 8+6x=4x+28 | | 3x/4-2=-10 | | 6x+3x+1=5 | | 1x-5=-2x+4 | | 17+3x-14-x=21 | | x-7=7x-41 | | 25a^2=1000 | | 5x/2-1=-31 | | 4-3x+11+9x=45 | | 25a=100 | | 3-8=-1x+2x | | 5x+2=5(x-2) | | 8n+20=3n+10 | | 3x+9=4x+12 | | t(2t-1)=0 | | 12x+23-7x=98 | | 119-2x=16x+19 | | -2x+3=-2x+3 | | -10+5x=x-26 | | 3(2x+4)=2(9+2x) | | 8-7x=98-28x | | 6a+23+7=0 | | 5=7 | | 7-3x=17+2x | | -2x+10=-80+7x |